Analisis Pengaruh Leverage, Likuiditas, Intensitas Modal, Dan Debt Covenant Terhadap Konservatisme Akuntansi (Studi Kasus Pada Perusahaan Manufaktur Sub-Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Fajar Abimanyu; Mujiyati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the influence of leverage, liquidity, capital intensity, and debt covenant on accounting conservatism in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. A quantitative approach was employed using hypothesis testing methods. The sampling technique used purposive sampling with specific criteria, and the data analyzed were secondary data obtained from annual financial reports. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests. The results indicate that leverage and debt covenant have a significant effect on accounting conservatism, while liquidity and capital intensity have no significant influence. The adjusted R-square value of 0.110 indicates that only 11% of the variation in accounting conservatism is explained by the independent variables in this study.